(3Yjhf GdCUhds - (3GdHQZGfj , eMeO UGdM Hf eMeO GdHQZGfj GdbRhjfj,J (B1281 (3g` s ((3eSGcf GHQGgje CHGO s)
(3ChdgG (B:s
(3CeG HYO ajbhd GdabjQ GdeJYWT Edi Efi cfJ ai YfahGf THGHi NGFVkG ai af GdCUhd s
(3BNQgG (B:s
(3Pdc eVGakG Edi TgGOI GdYOhd hceGd GYJeGO GdeLdSjf s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B164 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B86s
Keywords: (3abg GdePGgH GdCNQis